Novel,practical and cheap source for isolating beneficial Î³-aminobutyric acid-producing leuconostoc NC5 bacteria. - Othman Ali, Farrah Wahida; Abdulamir, Ahmed Sahib; Mohammed, Abdulkarim Sabo; Abu Bakar, Fatimah; Abdul Manap, Yazid; Zulkifli, Anwarul Hidayah; Saari, Nazamid (Medwell Publishing, 2009)
GABA is well known for its physiological functions as antioxidant, diuresis, tranquilizer, anti-hypertensive, epilepsy treatment and diabetic prevention. Most of the fermented food products are known and proven for its high content GABA producer, which contributes the food as potential functional foods. Among 5 positive isolates from the Malaysian commercial fermented shrimp product (cincaluk), only one strain of bacteria showed the highest GABA-producing activity. Leuconostoc NC5 showed the highest production ability of both extracellular and intracellular GABA content (2.84±0.19 mM, respectively) with GAD activity at 1.93±0.37 unit. The effect of cultivation time, temperature, pH and different concentration of glutamate, carbon source, nitrogen source and Pyridoxal-5’-Phosphate (PLP) on the production of GABA was investigated. This study concludes that the optimum conditions for GABA production were recorded at the cultivation temperature of 37°C, pH 5.0 and cultivation time at 168 h. Furthermore, the addition of PLP and nitrogen source to the culture medium significantly increased GABA production by 30-fold. Thus, Leuconostoc NC5 can be a potential starter culture for GABA-enriched functional foods. This strain showed a potential of being starter culture for the production of fermented functional foods containing GABA.